2021
DOI: 10.1017/dmp.2021.117
|View full text |Cite
|
Sign up to set email alerts
|

Bed Surge Capacity in Saudi Hospitals During the COVID-19 Pandemic

Abstract: Objectives To assess the hospital beds and intensive care unit (ICU) beds with a ventilator surge capacity of the health system in Kingdom of Saudi Arabia (KSA) during COVID-19 pandemic. Methods This study used relevant data from the National Health Emergency Operation Center to estimate general hospital and ICU beds surge capacity and tipping points under three distinct transmission scenarios. Results The study results reveal that hospitals in the KSA need to be suppli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In the KSA, a strategic approach was implemented whereby patients are referred to private hospitals, with the costs being covered by the Saudi government, regardless of nationality or residential status. A further policy addition was the designation of speci c healthcare facilities as reference centers, as well as the development of a system for daily monitoring of isolation bed occupancy in order to facilitate timely decisions for bed expansions or patient transfers to neighboring facilities [27]. This policy is designed to manage ICU capacity effectively, ensuring that there is su cient space available in these critical care units during this crisis and any future crisis.…”
Section: Variations In Icu E-referral Characteristics In Generalmentioning
confidence: 99%
“…In the KSA, a strategic approach was implemented whereby patients are referred to private hospitals, with the costs being covered by the Saudi government, regardless of nationality or residential status. A further policy addition was the designation of speci c healthcare facilities as reference centers, as well as the development of a system for daily monitoring of isolation bed occupancy in order to facilitate timely decisions for bed expansions or patient transfers to neighboring facilities [27]. This policy is designed to manage ICU capacity effectively, ensuring that there is su cient space available in these critical care units during this crisis and any future crisis.…”
Section: Variations In Icu E-referral Characteristics In Generalmentioning
confidence: 99%
“…They were overall unprepared to respond to a public health emergency such as COVID-19, and due to the unprecedented nature of the novel coronavirus, had insufficient time and resources to adapt, facing the pandemic with limited effective resources available [ 4 , 5 , 6 , 7 , 8 ]. Limited or inadequate medicines, equipment, personnel, and facilities were reported [ 9 , 10 , 11 ]. Appropriate service delivery was further compounded by ineffective public health policies and initiatives [ 12 ], financial instability, and health information and communication challenges [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 To accommodate higher demand, ICU capacity has surged internationally, generating an ever-increasing cohort of ICU admissions. [4][5][6] Nonetheless, owing to advances in ICU technology and care, the survival rate has increased considerably in ICUs [7][8][9] and the focus has shifted gradually to the long-term outcomes of survivors. 3 8-10 However, the effect of long-term complications after critical illness is overwhelming and multidimensional so ICU survivorship can have profound consequences.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely to be worsened in the current COVID-19 pandemic, it was reported that 20% of confirmed cases demand ICU care 3. To accommodate higher demand, ICU capacity has surged internationally, generating an ever-increasing cohort of ICU admissions 4–6. Nonetheless, owing to advances in ICU technology and care, the survival rate has increased considerably in ICUs7–9 and the focus has shifted gradually to the long-term outcomes of survivors 3 8–10.…”
Section: Introductionmentioning
confidence: 99%